Application of life cycle assessment in process design: case study on SO₂ abatement technologies in the PGM sector - Munyongani, Veronica (Department of Chemical Engineering, 2017)
Platinum group elements (PGEs) are increasingly being used in a variety of environmentally-related technologies such as catalysts and catalytic converters which have strong expected growth to meet environmental and technological challenges this century. The platinum industry is actively seeking to progress its commitment to sustainability principles by reducing the negative impacts of their mining and mineral processing operations. Technical innovation to improve future plant designs, as well as the development of management policies, guidelines and protocols for efficient operation of process plants has therefore become a strategic priority for the South African platinum industry. The industry has also made an effort to understand the environmental impacts of its products from mine to metal, using life cycle methods. However, very limited research has been done to investigate what environmental value could be created if strategic and design decisions in minerals processing were life cycle based, particularly in the context of PGMs. Seminal work by Stewart (1999) investigating the environmental life cycle consideration for design-related decision making in the minerals industry has not led to significant adoption. Forbes et al. (2000) analysed metal processing using LCA and were able to identify opportunities for improved environmental performance. They however did not explore how it would be incorporated into the decision making cycle. Therefore, the main objective of this research is to determine whether life cycle assessment could help inform design decision making in the minerals industry. In the years 2002-2008 several PGM-producing companies commissioned new SO₂ scrubbing technologies to meet the regulations that had been set to prevent the release of excessive amounts of sulphur dioxide from smelters in the Rustenburg area, a mining town located in the North West Province of South Africa. Using these cleanup process retrofits as case studies, this dissertation aims to determine whether the introduction of LCA as an environmental analysis tool would have provided additional value to the decision makers. The case study approach that was chosen compared and assessed the performance of SO₂ abatement technologies and the effect of efficiencies chosen on environmental performance by using life cycle assessment modelling. By doing the life cycle assessment on the different options that the companies had, it was possible to evaluate the indirect environmental impacts that could have been overlooked during the design decision making process. In addition , experts who were involved in the design processes of the SO₂ abatement retrofits were interviewed to establish: i) how the design decisions were made and ii) whether the life cycle based insights into technology performance would have been of use in the design work. The goal of the life cycle assessment was to identify whether there were design decisions that induced environmental burden shifting when platinum smelters in the Rustenburg area added SO₂ abatement technologies to their processes, which could have been avoided had the LCA perspective been taken into account. The assessments considered two key variables, namely extent of recovery and technology choice.